O livro didático de língua portuguesa e o novo ensino médio: um estudo sobre língua e identidade - Silva, Nathalia Aquino e (2023)
Linguistic heterogeneity is an undeniable phenomenon in Brazilian Portuguese and must therefore be considered a constitutive part of the teaching practice of Portuguese language teachers, as well as the teaching materials adopted by them. Given this, the main objective of this research is to analyze the linguistic treatment given to teaching about language and identity in the New High School, in order to propose a pedagogical notebook consisting of study material around the relationship between language and identity from a sociolinguistic perspective. . To this end, we selected as specific objectives to address the conceptions about language, norms, linguistic variation and teaching in the textbook in dialogue with the BNCC, analyzing how the BNCC's guidelines on these themes are presented in the textbook; investigate how the section of the Teacher's Manual guides teaching practice when working with the topic of interest to us; reflect on the importance of a variationist pedagogy for teaching Portuguese. The theoretical foundations of our research permeate the assumptions of the concept of identity(ies) – Stuart Hall (2006), Educational Sociolinguistics – Bortoni-Ricardo (2004, 2014), the foundations of linguistic variation and concepts linked to linguistic beliefs and attitudes – Labov (2008); Lambert; Lambert (1975); in addition to the discussion on linguistic norms with contributions and conceptions from many authors, of which we highlight Bagno (2003) and Faraco (2008). The material selected as the research corpus is the book Estações Língua Portuguesa: routes of social action referring to object 2/PNLD/2021, by the publisher ática, adopted by a public school included in the New Secondary Education. The result of the corpus analysis showed that there are few sections and activities presented that specifically deal with the relationship between language and identity, norms, variation, beliefs and linguistic attitudes. Specifically regarding linguistic variation (VL), we found that it is given secondary space and, when approached, it is very superficial in terms of reflection on the cultural, social and political aspects that have such an impact, above all, on the student's linguistic self-valuation. and your community. With this research, we hope not only to ensure the place for reflection on the relationship between language and identity, but also to present a didactic alternative that develops the student's political, social, cultural and linguistic awareness, especially those in high school in public schools.